Igf2 imprinting does not require its own DNA methylation or H19 RNA - Jones, Beverly K. (Cold Spring Harbor Laboratory Press, 1998)
Three models have been proposed to explain the imprinting of the mouse Igf2 gene on the maternal chromosome. We ruled out the importance of DNA methylation at Igf2 by showing that silencing of Igf2 accompanying the loss of DNA methylation could be overcome by a mutation at the neighboring H19 gene that activates Igf2. By replacing the H19 structural gene with a protein-coding gene, we have ruled out a role for H19 RNA in the imprinting of Igf2. This replacement resulted in sporadic activation of the H19 promoter on the paternal chromosome without affecting the level of expression of Igf2, a finding that is inconsistent with strict promoter competition between the genes. We conclude that a transcriptional model involving access to a common set of enhancers shared between Igf2 and H19 is the most likely explanation for Igf2 imprinting.